THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND COMPETENCE LEADERSHIP ON INNOVATIVE WORK BEHAVIOR: A MEDIATED MODEL - TUBEL, AGUSVEN; MOHAMAD SHAH, KASSIM; HELEN TAN, SUI HONG (UNIMAS Publisher, 2024)
This paper aims to delve into key elements that encourage teachers to participate in innovative work practices within a fiercely competitive setting. Current studies on the evolution of the fundamental mechanisms and limiting factors that explain the relationship between transformational leadership and leadership competencies in innovative work behavior are mediated by organizational citizenship behavior, knowledge sharing, employee voice, and organizational communication. The framework of this study is based on social exchange theory (SET) and conservation of resources theory (COR). PLS-SEM along with Smart PLS version 3.0 software was adopted for data analysis, which includes analysis of measurement models and structural models. The questionnaires were distribute to 299 teachers in the Riau Islands province. Data analysis showed that competence leadership, organizational citizenship behavior, and organizational identification further enhance innovative work behavior among teachers. However, the results further revealed that transformational leadership, knowledge sharing, and employee voice do not affect innovative work behavior. Additionally, this study found the influence of organizational identification as a mediator on the relationship between competency leadership and innovative work behavior, organizational citizenship behavior as a mediator for the relationship between transformational leadership and innovative work behavior, and organizational identification as a mediator for the relationship between transformational leadership and innovative work behavior among teachers. The current research provides useful insights regarding transformational leadership and leadership competencies that can generate positive energy in secondary school teachers in the Riau Islands, Indonesia, thereby encouraging innovative thinking.